Struktur Komunitas Mikroartropoda Tanah Di Hutan Wisata Gonoharjo Kecamatan Limbangan Kabupaten Kendal - Nugroho, Nindya Putra Wahyu; Rahadian, Rully; Hadi, Mochamad (Bioma : Berkala Ilmiah Biologi, 2013)
The study on community structure of soil microarthropod in Gonoharjo Tourism Forest has been done. The objective of this research are to compare community structure of soil microartropod and to know the effect of abiotic environmental factors on abundance of soil microarthropod in Tourism Forest of Gonoharjo. This research was conducted using transect method in four sampling locations i.e., coffe vegetation, pine vegetation, mixed vegetation in hot spring water area, and mixed vegetation of riverside area. Soil sampling were used soil corer, and then the sample were extracted using barlese-tullgren. The finding shows 4 Sub Orders and 22 Families from 10 Orders. Acari was the most dominant group in each observed locations. The most diverse was found in mixed vegetation on hot spring water area, while the least one was found in coffe vegetation. Then, the highest evenness index was found in mixed vegetation on riverside area, while the lowest evenness was found in coffe vegetation. Moreover , the richest soil microarthropods found in mixed vegetation on hot spring water area and the lowest richness was found in mixed vegetation on riverside area. Statistically, abiotic environmental factors that have big impact on soil microarthropod abundance were soil organic matter, soil pH, and soil moisture.